Semiquantitative analysis of intrahepatic CC-chemokine mRNas in chronic hepatitis C. - Nischalke, Hans Dieter (2004)
BACKGROUND: The mechanisms leading to hepatic injury in chronic hepatitis C virus (HCV) infection are only incompletely understood. Recent data propose a correlation of the intrahepatic expression of the CC chemokine RANTES and the degree of periportal and portal inflammatory liver damage. AIM: Here, we have studied the intrahepatic mRNA levels of CC chemokines RANTES together with that of other members of this chemokine family (MIP-1beta, MCP-1, and MCP-2) in chronic hepatitis C as compared with healthy controls. METHODS: Liver samples from 22 HCV-infected patients, nine individuals with primary biliary cirrhosis and from 12 normal controls were included into this study. Intrahepatic mRNA levels of CC chemokines RANTES, MIP-1beta, MCP-1, and MCP-2 were analyzed by a semi-quantitative reverse transcription/real-time polymerase chain reaction assay. RESULTS: In chronic HCV infection, intrahepatic RANTES mRNA levels were significantly higher than in non-infected controls (7.2-fold, p < 0.001) or in the disease control group (2.8-fold, p < 0.001) and higher levels of RANTES mRNA levels were observed in livers with an advanced stage of liver cell injury (histologic activity index > or = 6), although this difference was not statistically significant (p = 0.08). In contrast, mRNA levels of MIP-1beta (p = 0.021) and MCP-1 (p = 0.021) were significantly lower in HCV liver samples while MCP-2 expression was similar in all groups analyzed. CONCLUSION: The data support the concept of chemokines as mediators of liver cell injury in chronic hepatitis C.